Adaptasi Empat Klon Harapan Vanili di Kebun Percobaan Natar Lampung - Laba Udarno; Endang Hadipoentyanti (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
Indonesia is one of the main vanilla producers in the world. For the position maintain that effort needed to increase compatitive advantage of production and quality. The observation results of genetic resources obtained 4 promising high yield clones of vanilla. To obtain superior variety need adaptation test for 4 promising clones. The objectivities of research to obtain the vegetative and generative characters 4 promising clones of vanilla. Adaptation test of 4 promising vanilla clones (clone 1-4) were conducted at Natar experimental garden Lampung. The research was conducted using Randomized Block Design, with 6 replications, each treatment are 20 plants. Plant spacing was 1,50 X 1,25 m. parameters observed were plant height, stem diameter, leaf length, leaf width and tickness, internode length and root holding. The generative characters obesreved were numbers of bunches per plant, number of flowers per bunches, number of fruits per bunches, bean length and diameter. The result showed that second harvest (plant age is 5.7 years old), the greater number of bunches per plant was clones 3 (6,61). The greater flower per bunches was clone 4 (21,35 flowers), while the number of bean per bunches maintained only 12. The longest of fruit was clone 1 (18,22 cm).